In vitro metabolism of testosterone in the horse liver and involvement of equine CYPs 3A89, 3A94 and 3A95. Issue 4 (31st January 2014) - Schmitz, A.; Zielinski, J.; Dick, B.; Mevissen, M.
<x xml:space="preserve">Abstract</x> Testosterone (TES) 6‐β‐hydroxylation is a significant metabolic step in the biotransformation of TES in human liver microsomes and reflects cytochrome P450 (CYP) 3A4/5 specific metabolic activity. Several CYP3A enzymes have been annotated in the horse genome, but functional characterization is missing. This descriptive study investigates TES metabolism in the horse liver in vitro and the qualitative contribution of three CYP3A isoforms of the horse. Metabolism of TES was investigated by using equine hepatocyte primary cultures and liver microsomes. Chemical inhibitors were used to determine the CYPs involved in TES biotransformation in equine microsomes. Single CYPs 3A89, 3A94, and 3A95, recombinantly expressed in V79 hamster lung fibroblasts, were incubated with TES and the fluorescent metabolite 7‐benzyloxy‐4‐trifluoromethylcoumarin (BFC). The effect of ketoconazole and troleandomycin was evaluated on single CYPs. Testosterone metabolites were analyzed by HPLC and confirmed by GC/MS. In hepatocyte primary cultures, the most abundant metabolite was androstenedione (AS), whereas in liver microsomes, 6‐β‐hydroxytestosterone showed the largest peak. Formation of 6‐β‐hydroxytestosterone and 11‐β‐hydroxytestosterone in liver microsomes was inhibited by ketoconazole, troleandomycin, and quercetin. Equine recombinant CYP3A95 catalyzed 11‐β‐hydroxylation of testosterone (TES). Metabolism of BFC was significantly inhibited by ketoconazole in CYP3A95, whereas troleandomycin affected the activities of CYP3A94 and CYP3A95. Both inhibitors had no significant effect on CYP3A89. Metabolic reactions and effects of inhibitors differed between the equine CYP3A isoforms investigated. This has to be considered in future in vitro studies.